2017
DOI: 10.5005/jp-journals-10024-2000
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Differences between Dentists and Patients about Relative Quality of Metal Ceramic Restorations placed in the Esthetic Zone

Abstract: Introduction: Esthetic perceptions could differ between the dentist and his patients among various regions and cultures.Aim: The aims of this study were to evaluate the subjective differences between the dentist and the patient in terms of esthetics of metal-ceramic crowns (MCcs). The study also aims to compare the mesiodistal (MD) and buccolingual (BL) dimensions of the cemented crown with its respective natural antimeric tooth. Materials and methods:A total of 85 patients seeking treatment for a single crown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This indicates that the higher education increases awareness for a person and desire for better esthetic restorations. Studies have shown greater acceptability for anterior zirconia crown among the higher educated people [19][20][21] . Hence, these findings indicate that higher self-satisfaction for dental aesthetics are observed in participants with higher academic titles.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the higher education increases awareness for a person and desire for better esthetic restorations. Studies have shown greater acceptability for anterior zirconia crown among the higher educated people [19][20][21] . Hence, these findings indicate that higher self-satisfaction for dental aesthetics are observed in participants with higher academic titles.…”
Section: Discussionmentioning
confidence: 99%
“…PFM restorations represent the most widely used restorative technique in fixed prosthodontics, and their popularity may be due to their clinical longevity, accepted aesthetics, familiarity among most dental technicians, and cost. 25 , 26 In the third case, a zirconia core with facial cut by lithium disilicate glass ceramic (e.Max) was considered because the patient is a consumer of different beverages. This CAD/CAM material shows color stability for such patients, 27 , 28 and it is the most preferred material used by general practitioners in SA.…”
Section: Discussionmentioning
confidence: 99%
“…An excessively prominent ridge more commonly present in maxilla than mandible. 1 Its very challenging to fabricate the complete denture when the ideal biological consideration of both hard and soft tissues are not fullfilled. 2 Labially proclined maxilla with associated undercut is the most common condition that effects the esthetics and fabrication of complete denture.…”
Section: Introductionmentioning
confidence: 99%